Muhammad Sayyid Tantawi's Interpretation of the Verses of Riba - Alamsyah, Maulana Yusuf; Al-Obaidi, Khaleel (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2023)
The pattern of people's life has changed occasionally, encouraging people to follow this development, especially in matters related to mu’amalah. However, the problem here is that banking is synonymous with bank interest or rent, whereas most people in the community think that bank interest or rent is the same as usury. This paper is based on the results of a study that describes and classifies usury verses in the Qur’an, then analyzes them with the methodology used by Muhammad Sayyid Tantawi inTafsir al-Wasith, which was later linked to his fatwa regarding bank interest law. This study concluded that internal and external factors greatly influenced Tantawi's interpretation of bank interest in Islamic law, among which he used the opinions of modernist scholars such as Al-Alusy, Fazlur Rahman, etc. In addition, the pattern of interpretation of interpretation al-Wasith to the usury verse consists of four patterns consisting of sura al-Rum verse 39 explaining that transactions with usury will not develop and will even lose money. Surah al-Nisa' verses 160-161 demonstrate that their tyranny caused some of the painful sanctions Allah has ever bestowed upon the Jews as perpetrators of usury transactions.